Exploring Staff Nurses' Experiences of Head Nurse Supervisory Practices in Supporting Caring Practice Implementation in the Melati and Tuitan Inpatient Units of Kotamobagu City Regional - Linnie Pondaag; Jolie Febri Ponamon; Pingkan Christy Timbuleng; Ceril Pungus (Gayaku Publisher, 2026)
Background: Caring is a fundamental value in nursing practice that contributes to the quality of patient care and satisfaction. The implementation of caring practices among nurses can be influenced by various factors, including the supervisory role of head nurses. Effective supervision is expected to support not only technical performance but also the development of caring behaviors in daily nursing practice. Objective: This study aimed to explore staff nurses’ experiences of head nurse supervision in supporting the implementation of caring practices at Kotamobagu Regional Hospital. Methods: This study employed a qualitative research design with a descriptive phenomenological approach. The study was conducted in the Melati and Tuitan inpatient wards of Kotamobagu Regional Hospital. Eight staff nurses (IF1–IF8) were selected through purposive sampling. Data were collected through in-depth interviews and analyzed using content analysis. Results: The findings revealed three major themes: (1) supervision practices as routine managerial control focused on task completion and procedural compliance, indicating that supervision had not fully supported the relational aspects of nursing care; (2) limited reinforcement of caring behaviors during supervision, reflected in the minimal emphasis on therapeutic communication and emotional support; and (3) nurses’ dependence on supervisory direction in implementing caring practices, suggesting that caring behaviors had not yet been fully internalized as intrinsic professional values. These findings indicate that supervision remains predominantly task-oriented rather than caring-oriented. Conclusion: Head nurse supervision plays an important role in supporting nursing practice; however, current supervision is primarily focused on managerial and technical aspects. Caring values have not been consistently emphasized, resulting in limited reinforcement of caring behaviors among staff nurses. A more holistic supervisory approach is needed to integrate caring values into everyday nursing practice. Suggestion: Healthcare institutions and nursing managers should reorient supervisory practices by incorporating caring principles, therapeutic communication, reflective feedback, and emotional support into routine supervision activities. Continuous training and evaluation of supervisory competencies are also recommended to strengthen the integration of caring values within professional nursing practice.